Knowledge, Attitude and Practice of Diabetes Mellitus Type 2 Patients towards Compliance to Treatment in Pusat Kesehatan Masyarakat - Zahari, Asila Zahiri binti; Yunivita, Vycke; Martha, Januar Wibawa (Althea Medical Journal, 2016)
Background: Diabetes mellitus (DM) is one of the top ten chronic diseases in the world and the prevalence of this disease will increase in the future including in Indonesia. Treatment of DM needs collaboration between the patients and the providers to prevent multiorgan complications and increase the compliance to treatment. The correlation among the level of knowledge (K), attitude (A) and practice (P) plays an important role of patients towards compliance to treatment. The objectives of this study was to identify the level of knowledge, attitude and practice of DMT2 patient towards compliance to treatment at a primary care facility.Methods: This study was carried out by using cross sectional descriptive study from August until November 2013 in Public Health Center (Pusat Kesehatan Masyarakat/Puskesmas) Tanjungsari, Sumedang, West Java. There were 49 respondents and the sampling method used was non-probability sampling. The data was collected through face to face interview using questionnaire which consist of 27 questions about knowledge, attitude and practice. The collected data was anayzed using computer and was presented in the form of tables and a figure.Results: This study discovered that 22 patients had moderate knowledge, 17 patients had good knowledge and 10 patients had poor knowledge. As for attitude, there were 32 patients had good attitude and 17 patients had moderate attitude. Whereas, for practice, 44 patients were good and 5 patients were moderate.Conclusions: Majority of respondent had moderate knowledge, good attitude and practices. [AMJ.2016;3(3):416â20]DOI: 10.15850/amj.v3n3.871